The Staphylococcus aureus Extracellular Adherence Protein Eap Is a DNA Binding Protein Capable of Blocking Neutrophil Extracellular Trap Formation - Eisenbeis, Janina; Saffarzadeh, Mona; Peisker, Henrik; Jung, Philipp; Thewes, Nicolas; Preissner, Klaus T.; Herrmann, Mathias; Molle, Virginie; Geisbrecht, Brian V.; Jacobs, Karin; Bischoff, Markus (Frontiers in Cellular and Infection Microbiology, 2018)
The extracellular adherence protein (Eap) of Staphylococcus aureus is a secreted protein known to exert a number of adhesive and immunomodulatory properties. Here we describe the intrinsic DNA binding activity of this multifunctional secretory factor. By using atomic force microscopy, we provide evidence that Eap can bind and aggregate DNA. While the origin of the DNA substrate (e.g., eukaryotic, bacterial, phage, and artificial DNA) seems to not be of major importance, the DNA structure (e.g., linear or circular) plays a critical role with respect to the ability of Eap to bind and condense DNA. Further functional assays corroborated the nature of Eap as a DNA binding protein, since Eap suppressed the formation of “neutrophil extracellular traps” (NETs), composed of DNA-histone scaffolds, which are thought to function as a neutrophil-mediated extracellular trapping mechanism. The DNA binding and aggregation activity of Eap may thereby protect S. aureus against a specific anti-microbial defense reaction from the host.